COMPARATIVE STUDY OF JINAS IN JAUHARUL MAKNUN AND BALAGHAH WADIHAH ON MUALLAQAT: KOMPARASI TEORI JINAS DALAM JAUHARUL MAKNUN DAN BALAGHAH WADIHAH PADA MUALLAQAT - Nur Afifah; Rina Susanti (Muaddib: Journal of Arabic Language and Literature, 2025)
This article aims to examine the concept of jinās as presented in the classical Arabic rhetoric books Jauharul Maknūn and Balāghah Wāḍihah, as applied to the poetry of Mu‘allaqāt by Umru al-Qais. The author is particularly interested in the more concise classification of jinās found in Balāghah Wāḍihah, in contrast to the extensive categorization in Jauharul Maknūn by Imam al-Akhḍarī. This study adopts a qualitative descriptive method using a comparative literature approach. The findings reveal that the theory of jinās according to Jauharul Maknūn offers a more detailed and systematic classification of jinās types. Consequently, more examples of jinās from Jauharul Maknūn are identified in the Mu‘allaqātof Umru al-Qais compared to those classified using the perspective of Balāghah Wāḍihah. The analysis shows that there are 21 types of jinās based on Jauharul Maknūn and 17 types based on Balāghah Wāḍihah, with 19 identical lines (bayt) of poetry analyzed. This suggests that Jauharul Maknūn provides a broader and more nuanced framework for interpreting rhetorical figures in Arabic classical poetry. The study contributes to a deeper understanding of Arabic rhetorical theory and highlights the importance of classical sources in analyzing literary texts.